Collaborative Governance Dalam Pemberdayaan Kelompok Tani Di Kabupaten Wajo - Fatimah, Putri; Mahsyar, Abdul; Kasmad, Rulinawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to find out how collaborative governance  in empowering farmer groups in Wajo Regency. The method in this study was descriptive qualitative. The number of informants in the study was 8 people. The results of this study showed that the concept of Collaborative Governance had not been able to realize the empowerment of Farmer Groups. Institutions ran individually so that the network structure did not exist in collaboration, in terms of commitment from farmer groups did not know how to build commitment, in terms of building mutual trust between stakeholders was still lacking because they did not know how to build trust in collaboration, governance was not good because there were still differences opinion among stakeholders, then in terms of access to power and accountability was quite good, as well as in terms of sharing information had been going well, but in terms of human resources, techniques and finance had not been adequate.